ANALISIS PENGARUH PEMBIAYAAN KREDIT PERBANKAN, LAMA USAHA, DAN MEDIA PEMASARAN DIGITAL TERHADAP KEBERLANGSUNGAN USAHA MIKRO (STUDI KASUS USAHA MAKANAN DAN MINUMAN DI KOTA MALANG) - Evita Safitri; Farah Wulandari Pangestuty (Contemporary Studies in Economic, Finance and Banking, 2024)
This research aims to analyze the influence of banking loan financing , business age, and digital marketing media on micro-sized enterprises income in Malang City. This research uses quantitative research methods with linear regression analysis. The data used in this research uses primary data in the form of a questionnaire distributed to 99 respondents who are micro-sized enterprises in Malang City. This research found that the results of banking loan financing had a significant positive effect on the income of Food and Beverage enterprises  in Malang City, Business age had no significant effect on the income of food and Beverage enterprises in Malang City, and Digital marketing had a significant positive effect on the income of Food and Beverage enterprises in Malang City.